Tactical Project-Based Learning (T-PJBL) Model: A Pedagogical Engineering To Enhance Cadet Leadership at The Military Academy - Budi Harijanto; Lukito Edi Nugroho; Subando Agus Margono; Ambar Teguh Sulistyani (Asian Journal of Social and Humanities, 2026)
Contemporary military education positions high discipline as an operational foundation that not only ensures order but also serves as a crucial determinant of cadets' holistic academic achievement. This study aims to formulate an adaptive PjBL model, termed Tactical Project-Based Learning (T-PjBL), to enhance Cadet leadership competence. Employing an Explanatory Sequential Mixed Method, this study found that the low influence of standard PjBL on leadership (R Square 10.5%) was caused by external variables such as physiological fatigue and command culture rigidity. Through the integration of quantitative and qualitative data, the T-PjBL model was developed with five main phases: Mission Briefing, Tactical Planning, Command Timeline, Supervised Maneuver, and After-Action Review (AAR). The results indicate that pedagogical engineering through the T-PjBL model can synchronize academic activities with regimented service rhythms and mitigate Cadets' cognitive barriers. The study concludes that learning innovation in military environments requires contextual adaptation that respects doctrine and the learners' physical conditions.